Metabolic stress-induced cardiomyopathy is caused by mitochondrial dysfunction due to attenuated Erk5 signaling - Liu, Wei; Jungmann, Andreas; Müller, Oliver J. (Nature Communications, 2017)
The mechanistic link between metabolic stress and associated cardiomyopathy is unknown. Here the authors show that high fat diet causes calpain-1-dependent degradation of ERK5 leading to mitochondrial dysfunction, suggesting the maintenance of cardiac ERK5 as a therapeutic approach for cardiomyopathy prevention and/or treatment.